2016
DOI: 10.1590/1806-9282.62.02.171
|View full text |Cite|
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics of patients with diabetic foot ulcer

Abstract: The social demographic variables play an important role in diabetic foot ulceration. Given that the neuropathic ulcers are more easily preventable, systematic monitoring of patients with neuropathy is important. In patients with neuroischemic foot, strategies to cope or manage more efficiently the pain are paramount. Intervention should be multidisciplinary and take into account sociodemographic and clinical factors, as well as the presence, intensity and interference of pain in the patient's daily life activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 46 publications
2
27
0
9
Order By: Relevance
“…All these studies that analysed complications as a risk factor confirmed their significant negative impact. The link between the presence of coronary artery disease, particularly angina pectoris, with worse scores in all segments of SF-36 questionnaire was confirmed in many studies (6,(10)(11)(12). The study conducted by Lloyd et al showed that coronary heart-disease is usually connected with a significant reduction in QOL, particularly in the area of physical health (28).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…All these studies that analysed complications as a risk factor confirmed their significant negative impact. The link between the presence of coronary artery disease, particularly angina pectoris, with worse scores in all segments of SF-36 questionnaire was confirmed in many studies (6,(10)(11)(12). The study conducted by Lloyd et al showed that coronary heart-disease is usually connected with a significant reduction in QOL, particularly in the area of physical health (28).…”
Section: Discussionmentioning
confidence: 86%
“…Macrovascular complications such as cardiovascular, cerebrovascular and peripheral vascular disease result in physical disability and decreased HRQOL in these patients. A number of studies have shown that microvascular complications such as nephropathy, retinopathy and diabetic foot play a crucial role in patients' decreased physical and mental well-being (11)(12)(13)(14). Lower health-related scores are associated with these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Participants with longer duration of diabetes may have developed better adaptation strategies to self-manage diabetes compared to those with shorter duration of diabet (Alrahbi, 2014). Abubakari, Cousins, Thomas, Sharma and Naderali (2016) Therefore, health check/follow-up are quite important in evaluation of selfmanagement skills of diabetic patients on the management of the disease (Pedras et al, 2016;Xu, Pan and Liu, 2010). Majority of the patients (82%) in our study were found to attend to health check follow-ups.…”
Section: Discussionmentioning
confidence: 82%
“…discussion T2DM and its chronic complications have become increasingly common. 1,9,10 Thus, the importance of the survey carried out in our study, which contributes from a clinical point of view to the monitoring of diabetic patients.…”
Section: Resultsmentioning
confidence: 92%